Building Robots and Story‐Based Learning to Teach Cyber‐Physical Systems Effectively to Any Class of Audiences ranging from Elementary School Students to University Graduates. (November 2016) - Seya, Keisuke; Shirasaka, Seiko
Abstract: The Cyber‐Physical Systems (CPS) has attracted large attention from a wide variety of audiences such as academia, industry, and news media. That's because it is considered a key enabler of our future technologies. The governments of various countries have realized its importance and hammered out long‐term visions to invest their resources (i.e. time and money) to urge the growth of the CPS industry. In order to increase the number of people who can work in this industry, the demand searching for a new way of teaching CPS to different classes of people has emerged naturally. In order to help both learners and educators, we've developed a story‐based educational system for CPS that is extremely adaptable to any class of learners; it guides the learners to understand the CPS by building their own robot. In this paper, we describe the theory behind its design and discuss the effectiveness of this approach.